British Muslims Navigating between Individualism and Traditional Authority - Amin, Hira (Religions, 2019)
According to some sociologists, one of the hallmarks of modernity is the end of 'pre-determined' identities and its replacement with bricolage projects in which people literally create 'do-it-yourself' identities. This has also significantly impacted the religious sphere, where it has been argued that traditional authorities are constantly undermined by individualistic cultures, print media, rising literacy rates and, more recently, the internet. Through analysing online discussions, this article explores how some young, devout British Muslims navigate between individualism and their own personal understanding of Islam on the one hand and following traditional religious authority figures on the other. This article argues that British Muslims who are consciously trying to practise their faith are neither following traditional religious authoritative figures or institutions blindly nor fully rationalising and individualising their faith. Rather, they are involved in a complex process of choosing and self-restricting themselves to certain scholars that they believe are representative of Islam and thereafter critically engaging with the scholar and his or her verdicts by adding in their own opinions, experiences and even Islamic textual evidence. While this illustrates how religious authority is transforming in the age of new media, the persistent engagement with scholars also indicates how they still play a significant role in the shaping of Islam in Britain.